FUNGSI MUSIK DALAM UPACARA PERAYAAN RITUAL THAIPUSAM ETNIS HINDU TAMIL DI BANDA ACEH - Rika Wirandi; Magfhirah Murni B. P. (Gorga : Jurnal Seni Rupa, 2021)
Thaipusam is a celebration ceremony held sacredly in the form of a prayer ritual procession and the procession of the Lord Murugan statues which is held annually by the Tamil Hindu ethnic community in Banda Aceh. This ritual is held in the Thai month according to the Hindu Tamil calendar, as a form of respect for Lord Murugan for his victory in fighting evil. This celebration ceremony is also a place to fulfill vows and purify themselves for ritual participants - which is accompanied by the attraction of stabbing sharp objects into certain body parts such as the tongue, lips, cheeks, forehead, back, and other body parts. This celebration ceremony includes percussion music at the time of the procession. In addition to having multiple functions in the context of the celebration ceremony, percussion ensemble music in the procession is also believed to have its own effect on ritual participants. Religious songs and percussion music ensembles in the celebration ceremony at first glance do appear to be mere elements of ritual celebration. However, furthermore, the percussion music ensemble is considered to play a role in influencing the spirituality of the ritual performer to lead him to a state of stupor, to trance when performing body piercing attractions. The purpose of this study was to examine the function of music in the Thaipusam Ritual celebration ceremony as well as in influencing the spirituality level of the ritual participants. The research method used is a qualitative research method which is carried out in several stages, including: literature study and in-depth interviews. The approach used in this research is the theory of music function from Alan P. Merriam and the approach to music and trance proposed by Gilbert Rouget. The results of this study indicate that, at least there are four functions of music observed in this study, including: celebratory and entertainment functions; function of cultural expression; the function of legitimizing ritual ceremonies; and function of community group integrity. On the other hand, for ritual supporters – in this case the votive participants, music serves as a spiritual reinforcement for them in fulfilling their vows.Keywords: music function, thaipusam, Banda Aceh.AbstrakThaipusam adalah upacara perayaan yang diselenggarakan secara sakral dalam bentuk prosesi ritual doa dan prosesi araka-arakan arca Dewa Murugan yang diselenggarakan setiap tahun oleh masyarat etnis Hindu Tamil di Banda Aceh. Ritual ini dilangsungkan pada bulan Thai menurut kalender Hindu Tamil, sebagai bentuk penghormatan Dewa Murugan atas kemenangannya memerangi kejahatan. Upacara perayaan ini juga sebagai ajang untuk menunaikan nazar dan menyucikan diri bagi peserta ritual -- yang disertai atraksi menusukkan benda-benda tajam ke beberapa bagian tubuh tertentu seperti, lidah, bibir, pipi, dahi, punggung, serta bagian tubuh lainnya. Upacara perayaan ini menghadirikan permainan musik perkusi pada saat prosesi arak-arakan. Selain memiliki fungsi yang jamak dalam konteks upacara perayaannya, musik ensambel perkusi dalam arak-arakan juga diyakini memiliki efek tersendiri bagi peserta ritual. Nyanyian keagamaan dan ensambel musik perkusi dalam upacara perayaan tersebut secara sekilas memang tampak sebagai unsur pemeriah ritual semata. Namun, lebih jauh, ensambel musik perkusi tersebut dinilai berperan dalam memengaruhi spiritualitas pelaku ritual hingga mengantarnya ke pada kondisi kusyuk, hingga trance saat melakukan atraksi tindik tubuh. Tujuan penelitian ini untuk melihat fungsi musik dalam upacara perayaan Ritual Thaipusam serta dalam memengaruhi tingkat spiritualitas peserta ritual. Metode penelitian yang dipakai adalah metode penelitian kualitatif yang dilakukan dalam beberapa tahapan, di antaranya: studi literatur dan wawancara mendalam. Pendekatan yang digunakan dalam penelitian ini adalah teori fungsi musik dari Alan P. Merriam dan pendekatan tentang musik dan trance yang dikemukakan oleh Gilbert Rouget. Hasil penelitian ini menyatakan bahwa, setidaknya terdapat empat fungsi musik yang teramati dalam penelitian ini, di antaranya: fungsi pemeriah dan hiburan; fungsi ekspresi budaya; fungsi pengabsahan upacara ritual; dan fungsi integritas kelompok masyarakat. Di sisi lain, bagi pendukung ritual - dalam hal ini peserta nazar, musik berfungsi sebagai penguat spiritual mereka dalam menunaikan nazar.Kata Kunci: fungsi musik, thaipusam, Banda Aceh. Authors:Rika Wirandi : Institut Seni Budaya Indonesia AcehMaghfihrah Murni B. P. : Institut Seni Budaya Indonesia Aceh References:AcehKita.  (2018). Perayaan Maha Puja Pengguni Uthiram, Umat Hindu Tamil di Aceh. YouTube. https://www.youtube.com/watch?v=q1rwc294NwA.Acehkini. (2019). Prosesi Arakarakan. YouTube. Acehkini.id/https://www.youtube.com/watch?v=plj926dKupo.Ananda, Ferdian. (2016). Uthiram Pangguni Celebration in Aceh. YouTube. https://www.youtube.com/watch?v=L77hKkVZ7xA.Dwi, N. (2019). Festival Thaipusam Sebagai Daya Tarik Wisata di Batu Caves Malaysia.Karnaen, Y. (2017). Analisis Tari Bharatanatyam dan Musik Iringan pada Upacara Thaipusam Masyarakat Tamil di Kota Binjai.Merriam, A. P., & Merriam, V. (1964). The Anthropology of Music. Evanston: Northwestern University Press.Mogot, Y. (2019). Aktivitas Komunikasi Masyarakat Hindu Tamil Dalam Upacara Thaipusam Di Singapura. Jurnal Common, 3(2), 216–228.Moleong, L. J. (2007). Metodologi Penelitian Kualitatif Edisi Revisi. Bandung : PT Remaja Rosdakarya.Riyaf, A., & Hasanah, N. (2016). Anthropos: Jurnal Antropologi Sosial dan Budaya. Anthropos, 2(1), 46–61.Rouget, G. (1985). Music and Trance: A Theory of the Relations Between Music and Possession. Chicago: University of Chicago Press.Wirandi, Rika. (2020). “Vel yang Terdapat pada Kuil Pelani Andawer”. Hasil Dokumentasi Pribadi: 09 Juni 2020, Banda Aceh.